The Pseudomonas putida HskA hybrid sensor kinase responds to redox signals and contributes to the adaptation of the electron transport chain composition in response to oxygen availability. Issue 6 (19th July 2013) - Sevilla, Emma; Alvarez‐Ortega, Carolina; Krell, Tino; Rojo, Fernando
Summary Pseudomonas putida has a branched aerobic electron transport that includes five terminal oxidases, each of which has different properties. The relative expression of each oxidase is carefully regulated to assemble the most suitable electron transport chain for the prevailing conditions. The HskA hybrid sensor kinase participates in this control, but the signals to which HskA responds were unknown. Here, the influence of HskA on the mRNA abundance of genes coding for all terminal oxidases and for the bc1 complex was analysed in cells growing under controlled aerobic, semiaerobic or microaerobic conditions. The results indicate that the influence of HskA on the expression of each terminal oxidase and the bc1 complex varies depending on oxygen availability. This effect was more pronounced under aerobic or semiaerobic conditions, but decreased under microaerobic conditions. The expression of hskA was regulated by oxygen availability. We show that HskA autophosphorylation is inhibited by ubiquinone but not by ubiquinol, its reduced derivative. This suggests that HskA could sense the oxidation state of the respiratory ubiquinones, which may be a key factor in HskA activity. Inactivation of hskA reduced growth rate and oxygen consumption, stressing the importance of HskA for the assembly of an efficient electron transport chain.